HUBUNGAN RIWAYAT KEJANG DEMAM DENGAN KEJADIAN EPILEPSI DI RUMAH SAKIT PUSAT ANGKATAN DARAT GATOT SOEBROTO TAHUN 2020 - Shafiyya Naura Allika (2022)
Febrile seizures are seizures due to a rapidly increasing body temperature up to >38°C, and the increase in temperature is caused by extracranial mechanisms. Complex febrile seizures have a higher risk of recurrent febrile seizures and epilepsy later in life. The incidence of febrile seizures in Indonesia in 2012 - 2013 was 3-4%, it was reported that 6.5% among 83 febrile seizure patients became epileptic. In DKI Jakarta, research on the relationship between a history of febrile seizures and the incidence of epilepsy has not been published and is felt to be lacking. This study aims to determine the relationship between a history of febrile seizures and the incidence of epilepsy at Gatot Soebroto Hospital in 2020. This study was an analytical observational study with a cross sectional approach. The data source comes from medical records with the research sample being epilepsy patients at the neurology department of the Gatot Soebroto Hospital in 2020. The results showed that 35 people had epilepsy (36.1%) and 62 people did not have epilepsy (63.9%). The incidence of epilepsy was dominated by the adult age group (20-60 years) namely 22 people (31.9%) and female, namely 19 people (54,3%). Epilepsy accompanied by a history of febrile seizures was 14 people (40,0%). The results of the chi-square analytical test were p=0.002, a history of febrile seizures was statistically significant as a risk factor for epilepsy OR: 5.2 (95% Cl; 1.9-15). The conclusion in this study is that there is a relationship between a history of febrile seizures and the incidence of epilepsy at the Gatot Soebroto Army Hospital in 2020.